The Treasury's Experiment with Single-Price Auctions in the Mid-1970s: Winner's or Taxpayer's Curse? - Simon, David P. (The Review of Economics and Statistics, 1994)
This study examines the Treasury's experiment with single-price bond auctions in the mid-1970s and finds that, controlling for factors unrelated to auction technique, markups of auction average rates over when-issued rates shortly after auctions were a statistically significant seven to eight basis points higher at single-price auctions than at discriminating-price auctions. These results suggest that single-price auctions raised Treasury borrowing costs by roughly 3/4 percent of the issuing price of auctioned securities. Copyright 1994 by MIT Press.